ANALISIS MATERI PEMBELAJARAN BAHASA ARAB PADA BUKU AL-LUGHAH AL-‘ARABIYAH AL-MU’ÂSHIRAH DENGAN PENDEKATAN ASAS PENGEMBANGAN MATERI - Muhammad Ediyani (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2016)
This research is aimed to analyze the learning material on the book entitled al-Lughah al-‘Arabiyah al-Mu’ashirah written by Eckehard Schulz through principles of material development approach. And to reveal the advantages and disadvantages from material design. This research is library research by which a book entitled al-Lughah al-‘Arabiyah al-Mu’ashirah as research object. The research is conducted using observation method to the book both primary and secondary. The researcher uses content analysis in analyzing data. The result of this research shows that this book is already feasible and appropriate to be used as Arabic subject learning material for non-Arabic speakers. The advantages of the book entitled al-Lughah al-‘Arabiyah al-Mu’ashirah are that this book makes students able to master the language skills, language elements, and able to comprehend Arabic characteristics, and another theoretical aspect. While the disadvantage of this book is there is no interesting picture (visualization) that can rise special motivation in learning this book.